Analisis Rasio Keuangan Pada Bank Swasta Nasional - Widiastuti Murtiningrum (Aliansi : Jurnal Manajemen dan Bisnis, 2023)
The analysis was carried out in order to find out whether CAR, NPL, NIM, LDR have an influence on ROA on the IDX and the Financial Services Authority. The data used are Foreign Exchange BUSN from 2016 to 2022 with a total sample of 22 banks. Quarterly secondary data from the Financial Services Authority from 2016 to June 2022, with purposive sampling. Method of analysis of panel data with multiple linear regression analysis. Test the hypothesis with t-test, resulting that CAR, NPL, NIM and LDR have no effect on ROA. Simultaneously have a significant effect of CAR, NPL, NIM and LDR on ROA BUSN Foreign Exchange. Simultaneously ROA can be explained by CAR, NPL, NIM and LDR of 77.11%, the remaining 22.89% of the variables outside the variables.